COVID-19 vaccination hesitancy and willingness among pregnant women in Italy - Grazia Miraglia del Giudice; Lucio Folcarelli; Annalisa Napoli; Francesco Corea; Italo Francesco Angelillo; The Collaborative Working Group; Annalisa Agangi; Antonio Sciambra; Glenda Scognamiglio; Walter Longanella (Frontiers in Public Health, 2022)
BackgroundPregnant women, especially those with comorbidities, compared to those non-pregnant, have higher risk of developing a severe form of COVID-19. However, COVID-19 vaccine uptake is very low among them.MethodsAn anonymous questionnaire was administered to randomly selected women 18 years of age that were currently pregnant or had just given birth between September 2021 and May 2022 in the geographic area of Naples. Vaccine hesitancy was assessed using the vaccine hesitancy scale (VHS).ResultsA total of 385 women participated. Women who had not been infected by SARS-CoV-2 and who needed information about vaccination against COVID-19 had a higher perceived risk of being infected with SARS-CoV-2. More than half (54.3%) of the women were very afraid of the potential side effects of the COVID-19 vaccination on the fetus. There was higher concern of the side effects of the vaccine on the fetus among those who did not have a graduate degree, those with high-risk pregnancy, those who had not been infected by SARS-CoV-2, those who were more concerned that they could be infected by SARS-CoV-2, those who did not know that this vaccination was recommended for them, and those trusting mass media/internet/social networks for information. Only 21.3% were vaccinated when pregnant, mostly women with a university degree, those who had been infected by SARS-CoV-2 before pregnancy, those who did not need information, and those who acquired information about the vaccination from gynecologists. Almost three-quarters (71.9%) were willing to receive the vaccination and those more likely were those with a university degree, those who have had at least one relative/cohabitant partner/friend who had been infected by SARS-CoV-2, those who were more concerned that they could be infected by SARS-CoV-2, and those who were not extremely concerned of the side effects of the vaccine on the fetus. A total of 86.4% were highly hesitant. Highly hesitant were respondents who did not get a graduate degree, those less concerned that they could be infected by SARS-CoV-2, and those trusting mass media/internet/social networks for information.ConclusionPublic health efforts and education campaigns for pregnant women are needed for changing their perception patterns and for supporting gynecologists in promoting the uptake of this vaccination.